The influence of the electrical field on structures dimension measurement in electrostatic force microscopy mode - Sikora, Andrzej (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Electrostatic force microscopy (EFM) is one of important tools for diagnostic of surface electric properties on micro- and nanoscale. Its usefulness can be particularly seen when the development of new devices or materials is considered and its electric behavior is to be investigated. Due to the accessibility to both the height and the electrostatic distribution in two-dimensional data matrix, one can easily correlate the topography and electric properties of the surface. It is common that experienced AFM users pay attention to the presence of artifacts, but generally only the influence of the height signal on the EFM signal is considered. In the article, the influence of the electrostatic force on the measurement accuracy of structure dimensions will be shown. Also, the way of avoiding the misinterpretation of data will be proposed.
Optica Applicata, Vol. 39, 2009, nr 4, s. 933-941
Keywords: optyka; atomic force microscopy (AFM); electrostatic force microscopy (EFM); dimensions measurement accuracy